Evaluation оf the Protective Properties of Filtering Half-Masks by Measuring Pressure Difference - Golinko, V.I.; Cheberiachko, S.I.; Yavorska, O.O. (Наука та інновації, 2018)
Introduction. An important characteristic of respirator is the capability of its half-mask to protect the respiratory organs against the surrounding contaminated atmosphere due to a tight half-mask-face contact. Problem statement. Keeping a constant pressure difference under the mask is a low-cost and simple method of alternative diagnostics of half-mask protective properties involving special-purpose test aerosols. The method is based on the determination of the air amount entrained through the gaps while generating rarefaction within the under-mask area. However, there have been no recommendations on the use of the method for evaluating the insulating properties of lightweight filtering half-masks from under which it is impossible to evacuate air. Purpose is to represent a simplified method with measuring the rarefaction under a filtering half-mask making possible to determine its insulating properties and protection coefficient. Materials and Methods. Protection coefficient of respirator can be evaluated in terms of air amount passing through the filtering material and gaps with the preset coefficient of penetration and suction. The latter is calculated as coefficient of aspiration into the gap of the preset length. Air consumption is determined experimentally as pressure difference between the half-mask mounted tightly on a dummy and the tubes of preset diameter positioned along the obturation line. Results. A calibration line of the relation between the pressure difference and the air consumption through a gap for the filtering half-masks has been developed. Coefficients of insulation and protection of Lepestok-type respirators have been calculated. The protection coefficients have been established to proportionally depend on the ratio of air consumption through a filter and gaps between the face and the half-mask along the obturation line. Conclusions. It has been proved that the methods for determining the protective properties of filtering half-masks in terms of measuring pressure difference may be used as a low-cost alternative to expensive diagnostics of the quality of respiratory protective devices. Also, they can be employed for selecting and training workers to properly use the respirators under manufacturing conditions in accordance with EN 529:2006 requirements. Вступ. Важливою характеристикою респіратора є здатність його напівмаски захищати органи дихання від різноманітних забруднень в атмосфері за рахунок щільного прилягання до обличчя. Проблематика. Одним з низьковартісних і простих методів альтернатив діагностики захисних властивостей напівмасок за допомогою спеціальних тест-аерозолів є підтримання постійного перепаду тиску під маскою. Він базується на визначенні кількості повітря, що підсмоктується через щілини, при створенні розрядження у підмасочному просторі. Однак, немає рекомендацій щодо можливостей цього методу в оцінюванні ізолюючих властивостей легких фільтруючих напівмасок, з-під яких не можна відкачати повітря. Мета. Розробити спрощений метод оцінювання захисних властивостей напівмасок з використанням вимірювання ступеню розрідження повітря під фільтрувальною напівмаскою, який дозволяє встановити її ізолюючі властивості та коефіцієнт захисту. Матеріали й методи. Коефіцієнт захисту респіратора можна оцінити за кількістю повітря, що проходить через фільтруючий матеріал і щілини з відомим коефіцієнтом проникнення і підсосу. Останній обчислюється як коефіцієнт аспірації в щілину відомої довжини. Витрати повітря визначаються експериментально за різницею тисків між герметично розташованою напівмаскою на манекені та розташованими по її периметру обтюрації трубочками з відомим діаметром. Результати. Побудована калібрувальна шкала взаємозв’язку перепадів тиску і витрат повітря через зазор для фільтруючих напівмасок. Розраховано коефіцієнти ізоляції та захисту респіраторів типу «Лепесток». Встановлено, що коефіцієнт захисту прямопропорційно залежить від співвідношення витрат повітря через фільтр і щілини між обличчям і напівмаскою по смузі обтюрації. Висновки. Доведено, що метод визначення захисних властивостей фільтруючих напівмасок вимірюванням перепадів тиску можна використовувати як альтернативу високовартісній діагностиці якості засобів індивідуального захисту органів дихання, а також застосовувати при підборі та навчанні працівників правильній експлуатації респіраторів на виробництві відповідно до вимог ЕN 529: 2006. Введение. Важной характеристикой респиратора является способность его полумаски ограждать органы дыхания от различных загрязнений атмосферы за счет плотного прилегания к лицу. Проблематика. Одним из недорогих и простых методов альтернативой диагностики защитных свойств полумасок с помощью специальных тест-аэрозолей является поддержание постоянного перепада давления под маской. Он основан на определении количества подсасываемого воздуха через зазоры при создании разряжения в подмасочном пространстве. Однако, нет рекомендаций о возможности оценить с помощью этого метода изолирующие свойства легких фильтрующих полумасок, из-под которых нельзя откачать воздух. Цель. Разработать упрощенный метод оценки защитных свойств полумасок с использованием измерения разрежения воздуха под фильтрующей полумаской, позволяющий установить ее изолирующие свойства и коэффициент защиты. Материалы и методы. Коэффициент защиты респиратора можно оценить по количеству проходящего воздуха через фильтрующий материал и зазоры с известным коэффициентом проникания и подсоса. Последний вычисляется как коэффициент аспирации в щель известной длины. Расходы воздуха определяются экспериментально по разности давления между герметически расположенной полумаской на манекене и с расположенными по ее периметру обтюрации трубочками с известным диаметром. Результаты. Построена калибровочная шкала взаимосвязи перепада давления и расхода воздуха через зазор для фильтрующих полумасок. Рассчитаны коэффициенты изоляции и защиты респираторов типа «Лепесток». Установлено, что коэффициент защиты прямопропорционально зависит от соотношения расходов воздуха через фильтр и зазоры между лицом и полумаской по полосе обтюрации. Выводы. Доказано, что метод определения защитных свойств фильтрующих полумасок по измерению перепадов давления можно использовать как альтернативу дорогостоящей диагностике качества средств индивидуальной защиты органов дыхания, а также использовать при подборе и обучении работников правильной эксплуатации респираторов на производстве в соответствии с требованиями ЕN 529:2006.